2014
DOI: 10.4238/2014.april.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms associated with susceptibility to coronary artery disease in Han Chinese people

Abstract: ABSTRACT. This study investigated 5 single nucleotide polymorphism (SNP) haplotypes in susceptibility genes for coronary artery disease (CAD) and the putative involvement of these SNPs in CAD in the Chinese Han population. From March 2008 to June 2009, we selected 119 CAD patients and 115 subjects not related to the CAD of Chinese Han origin as controls. The SNP genotypes were performed by multiplex SNaPshot technology. The HNRPUL1 gene rs11881940T and GATA2 gene rs3803T loci were highly correlated with CAD (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Our results are consistent with these previous findings d. However, one previous study found no association of rs10757274 with CHD in a Han Chinese population (Shenzhen) [17]. The differences between our study and this study are likely due to differences in the two study populations.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with these previous findings d. However, one previous study found no association of rs10757274 with CHD in a Han Chinese population (Shenzhen) [17]. The differences between our study and this study are likely due to differences in the two study populations.…”
Section: Discussionsupporting
confidence: 92%
“…Rs1333049 was in the list of SNPs associated with MI, IHD based on the results obtained in a genome-wide study WNCCC, German MI Family study 8 . The association with IHD has been earlier shown for rs1333049 in the studies conducted in the United States, Portugal, China, Turkey, Iran 2, 20, 21, 22, 23, 27. The C allele of this SNP is also associated with an earlier onset of angina pectoris, MI, and early need in cardiovascular therapy, as has been shown by the study of IHD (Coronary Disease Cohort Study) and MI (Post-Myocardial Infarction) cohorts 24 .…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the divergence between Gata2 mRNA and protein levels could be differential posttranscriptional/ posttranslational regulation in distinct vascular beds; indeed, our earlier work documenting that miR-451 levels are elevated in primary embryonic BECs compared with LECs (3) provides one potential mechanism by which this could be accomplished. An important role for GATA2 in arteries may underlie the hemorrhagic phenotype of Gata2 ΔEC mice described by us and others, as well as the association of GATA2 SNPs in patients with early-onset coronary artery disease (9)(10)(11). Targeted mutation of gata2a in zebrafish has recently been demonstrated to result in defective morphogenesis of the dorsal aorta, resulting in arterial-venous shunts and suggesting that arterial defects could also contribute to the vascular phenotype observed in Gata2 ΔEC mice.…”
Section: Discussionmentioning
confidence: 99%
“…While several earlier studies implicated GATA2 in vascular development (5)(6)(7)(8), the lack of an obvious vascular phenotype in Gata2 -/-mice prior to their demise around E10.5 has precluded in depth analyses of Gata2 function in vasculogenesis and angiogenesis. SNPs in GATA2 have been associated with coronary artery disease (9)(10)(11), implying a role for GATA2 in arterial development, while ablation of gata2a in zebrafish affects morphogenesis of the dorsal aorta (12). Recent studies in which Gata2 was deleted in hematopoietic and endothelial cell compartments (13), or was disrupted due to mutation of an enhancer element important for endothelial Gata2 expression (14), suggested that Gata2 is important for vascular integrity and for efficient separation of the blood and lymphatic vascular networks (13,14).…”
Section: Introductionmentioning
confidence: 99%